2022
DOI: 10.1007/s10566-022-09703-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Korean Adolescents’ Dependence on Smartphones, Peer Relationships, and Life Satisfaction

Abstract: Background In recent years, the penetration rate of smartphones among Korean teenagers has increased, making it critical to clarify the influence of these devices on adolescents’ lives. Objective This study investigated the effects of smartphone dependence on peer relationships and life satisfaction among Korean adolescents. Methods Using the middle school panel of the Korean Children and Youth Panel Survey (KCYPS), longitudinal data of 2,250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Of the 43 articles included (Table 3), 31 were crosssectional [4, 57-60, 62-82, 87-89, 91, 95, 97] and only 10 longitudinal [61, 83-86, 90, 92-94, 96, 98] and 2 case-control studies were found [55,56]. Depressive symptoms were the most investigated wellbeing outcome (23 studies: [4, 56-67, 83-86, 88, 92-95, 97, 98]), followed by loneliness (10 studies: [55,56,62,[67][68][69][70][71][72]93]), life satisfaction (8 studies: [73][74][75][76][77][89][90][91]), selfesteem (6 studies: [66, 67, 78-80, 87, 93]), happiness (5 studies: [67,70,76,81,83,86]), and subjective wellbeing (5 studies: [78,79,82,91,96]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 43 articles included (Table 3), 31 were crosssectional [4, 57-60, 62-82, 87-89, 91, 95, 97] and only 10 longitudinal [61, 83-86, 90, 92-94, 96, 98] and 2 case-control studies were found [55,56]. Depressive symptoms were the most investigated wellbeing outcome (23 studies: [4, 56-67, 83-86, 88, 92-95, 97, 98]), followed by loneliness (10 studies: [55,56,62,[67][68][69][70][71][72]93]), life satisfaction (8 studies: [73][74][75][76][77][89][90][91]), selfesteem (6 studies: [66, 67, 78-80, 87, 93]), happiness (5 studies: [67,70,76,81,83,86]), and subjective wellbeing (5 studies: [78,79,82,91,96]).…”
Section: Resultsmentioning
confidence: 99%
“…As human beings, non-material social assistance from friends and significant others is a need that when fulfilled can significantly impact on our perception of life satisfaction as shown in several researches [165][166][167][168]. However, considering that all, but one [90], of the studies included in this review are crosssectional in nature [73-77, 89, 91], temporality could not be implied with high certainty. Further studies with a longitudinal design are needed to address the directionality concern, increase the validity of evidence, and better understand the mechanism that governs this relationship.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A higher score indicates a better peer relationship. This scale has shown good reliability in the Korean adolescent samples ( Lim, 2023 ), and the Cronbach's α was 0.808. Additionally, a 14-item tool by Kim and Kim (2009) was utilized to find the student-teacher relationship using the same Likert scale.…”
Section: Methodsmentioning
confidence: 96%
“…Particularly during the COVID-19 epidemic, there has been a significant increase in Internet usage among adolescents [ 5 , 6 , 7 ]. PIU can have various negative effects on adolescents’ developmental adaptation, including sleep disorders [ 8 ], academic performance decline [ 9 ], low self-efficacy [ 10 ], and subsequent impacts on peer relationships and life satisfaction [ 11 ], among others. Regarding potential confounding variables or the formation process of PIU, existing research mainly focuses on individual traits [ 12 ] and pre-existing environmental factors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%